Решите Уравнение:
(x+9)^2-x*(x+8)=1
(x-11)^2=(x-7)*(x-9)
(x-4)*(x+4)-(x+6)^2=-16
(1-3x)^2-x*(9x-2)=5

Ответ №1

здравствуй.

\boxed{1}\\\\(x+9)^2-x*(x+8)=1\\x^2+18x+81-x^2-8x-1=0\\10x+80=0\\10x=-80\\x=-8\\\\\boxed{2}\\\\(x-11)^2=(x-7)*(x-9) \\x^2-22x+121=x^2-16x+63\\x^2-22x+121-x^2+16x-63=0\\-6x=-58\\x=9\frac{2}{3} \\\\\boxed{3}\\\\(x-4)*(x+4)-(x+6)^2=-16\\x^2-16-x^2-12x-36+16=0\\-36-12x=0\\-12x=36\\x=-3\\\\\boxed{4}\\\\(1-3x)^2-x*(9x-2)=5\\9x^2-6x+1-9x^2+2x-5=0\\-4x-4=0\\-4x=4\\x=-1

удачи в учебе.

Оцените статью
Сервис вопросов и ответов для школьников | educatic.ru
Добавить комментарий